Tradycja i innowacja w sztukach Seneki z perspektywy genologicznej: czas i miejsce - Słomak, Iwona (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
This article aims to provide a systematic description of Seneca’s approach to the categories of time and place as potentially rooted in the Attic tradition. With regard to these categories, there is indeed a certain generic consistency within the set of preserved serious Greek and Roman plays. The perspective adopted here sheds also light on a number of innovations, which suggest that great caution should be taken when considering the Greek tragedy as a direct or indirect source of inspiration for Seneca.